Elucidation of toxicity pathways in lung epithelial cells induced by silicon dioxide nanoparticles. - Odu Okoturo-Evans; Agnieszka Dybowska; Eugenia Valsami-Jones; John Cupitt; Magdalena Gierula; Alan R Boobis; Robert J Edwards (PLoS ONE)
A study into the effects of amorphous nano-SiO2 particles on A549 lung epithelial cells was undertaken using proteomics to understand the interactions that occur and the biological consequences of exposure of lung to nanoparticles. Suitable conditions for treatment, where A549 cells remained viable for the exposure period, were established by following changes in cell morphology, flow cytometry, and MTT reduction. Label-free proteomics was used to estimate the relative level of proteins from their component tryptic peptides detected by mass spectrometry. It was found that A549 cells tolerated treatment with 100 µg/ml nano-SiO2 in the presence of 1.25% serum for at least 4 h. After this time detrimental changes in cell morphology, flow cytometry, and MTT reduction were evident. Proteomics performed after 4 h indicated changes in the expression of 47 proteins. Most of the proteins affected fell into four functional groups, indicating that the most prominent cellular changes were those that affected apoptosis regulation (e.g. UCP2 and calpain-12), structural reorganisation and regulation of actin cytoskeleton (e.g. PHACTR1), the unfolded protein response (e.g. HSP 90), and proteins involved in protein synthesis (e.g. ribosomal proteins). Treatment with just 10 µg/ml nano-SiO2 particles in serum-free medium resulted in a rapid deterioration of the cells and in medium containing 10% serum the cells were resistant to up to 1000 µg/ml nano-SiO2 particles, suggesting interaction of serum components with the nanoparticles. A variety of serum proteins were found which bound to nano-SiO2 particles, the most prominent of which were albumin, apolipoprotein A-I, hemoglobin, vitronectin and fibronectin. The use of a proteomics platform, with appropriately designed experimental conditions, enabled the early biological perturbations induced by nano-SiO2 in a model target cell system to be identified. The approach facilitates the design of more focused test systems for use in tiered evaluations of nanomaterials.